A Novel Use of Arthroereisis in the Adult Flat Foot. Issue 1 (19th August 2016) - Dega, Raman; Peek, Anna C.; Malagelada, Francesc; Clark, Callum I.
Category: Hindfoot Introduction/Purpose: The use of an arthroereisis screw is well described in the paediatric population for the correction of flexible flat feet. Here we present a case comparison series involving the use of an arthroereisis screw to augment reconstruction in adult patients with Tibialis Posterior Insufficiency. Methods: All patients (36 feet in 34 patients) underwent flexor digitorum longus transfer, reefing of the spring ligament and a translational medialising calcaneal osteotomy. In 23 cases the reconstruction was augmented with an arthroereisis screw (Kalix, Integra), which was removed 6 months later in all cases. The mean age was 58 years and most patients were female. Weight bearing radiographs were taken after removal of the implant and assessed using previously published parameters. Patients were evaluated at follow up using validated functional outcome questionnaires (MOXFQ, EQ-5D and a health VAS). Results: One patient in the group without augmentation went on to have a triple fusion 13 months after reconstruction. In both cohorts the calcaneal pitch was raised, Meary's angle decreased, the medial cuneiform height increased and the talonavicular coverage angle improved post-operatively compared to pre-operative measurements (p < 0.05, Wilcoxon Signed Rank tests). There was a trend towards better radiographic correction in the augmented group and the difference in correction of the talonavicular coverage angle was statistically significant (p < 0.05, Students T test). There was however no difference between the MOXFQ, EQ-5D and heath VAS scores between the two groups at mean follow up of 4 years. Conclusion: We conclude that the use of an arthroereisis screw is a promising adjunct to conventional reconstruction in tibialis posterior insufficiency.